A servo-control system for open- and closed-loop blood pressure regulation - Nafz, Benno; Persson, Pontus B.; Ehmke, Heimo; Kirchheim, Hartmut (American journal of physiology. Renal physiology, 1992)
An electropneumatic servo-control system is described that can reduce and control arterial blood pressure in experimental animals. The device has been proved useful in the analysis of pressure-dependent physiological processes and allows the following two modes of operation: 1) a conventional open-loop setting that will reduce arterial pressure to a preselected set point and 2) a closed-loop mode that enables an adjustment to a dynamic pressure set point (i.e., the controlled pressure is reduced to a constant value below a reference pressure). A pneumatic servo-control mechanism was chosen to provide minimal control latency. The accuracy of the system under physiological conditions is well within +/- 1 mmHg. The device can be useful in a number of studies demanding a precise regulation of local arterial pressure, such as experiments on blood flow autoregulation, arterial baroreceptor reflexes, and all experiments involving the study of pressure-dependent excretory and incretory functions of the kidney. The closed-loop setting is useful for studying physiological feedback systems.
Gesehen am 25.11.2025